South Boston, My Home Town The History of an Ethnic Neighborhood - O'Connor, Thomas H. (Northeastern University Press, 2019)
An engaging yet objective look at the 350-year old history of "Southie," a neighborhood that has survived largely unchanged since the early days of immigrant Irish families and old-time political bosses. Originally published by Quinlan Press in 1988 and reprinted by Northeastern University Press in 1994. With a new foreword by Lawrence W. Kennedy.